Drosophila starvin encodes a tissue-specific BAG-domain protein required for larval food uptake. - Coulson, M.; Robert, S.; Saint, R. (Genetics, 2005)
We describe a developmental, genetic, and molecular analysis of the sole Drosophila member of the BAG family of genes, which is implicated in stress response and survival in mammalian cells. We show that the gene, termed starvin (stv), is expressed in a highly tissue-specific manner, accumulating primarily in tendon cells following germ-band retraction and later in somatic muscles and the esophagus during embryonic stage 15. We show that stv expression falls within known tendon and muscle cell transcriptional regulatory cascades, being downstream of stripe, but not of another tendon transcriptional regulator, delilah, and downstream of the muscle regulator, mef-2. We generated a series of stv alleles and, surprisingly, given the muscle and tendon-specific embryonic expression of stv, found that the gross morphology and function of somatic muscles is normal in stv mutants. Nonetheless, stv mutant larvae exhibit a striking and fully penetrant mutant phenotype of failure to grow after hatching and a severely impaired ability to take up food. Our study provides the first report of an essential, developmentally regulated BAG-family gene.